(untitled) (Research, Society and Development, 2023)
Introduction: The perioperative patient may undergo physical and psychological changes, so he needs to be monitored by a multidisciplinary team. Among these professionals is the pharmacist, who has a significant role in promoting the rational use of medicines. For effective pharmacotherapy, a continuous, systematized and documented pharmacotherapeutic follow-up, in communication with the multidisciplinary health team and with the patient, is necessary. Therefore, this research had as main objective to apply a pharmacotherapeutic method (Dáder) adapted to the conditions of the hospitalized patient who underwent a surgical procedure and through this method to observe possible drug interactions during the pre and postoperative period and to identify the adverse effects in order to enable preventive actions. Methodology: The present study is cross-sectional and descriptive, with the guiding question: "How can the pharmacist’s role contribute to patient safety in the perioperative period with the multidisciplinary team?" Results and Discussion: Fifty-three surgical patients participated in the study, of which 60.4% (32) were male and 39.6% (21) were female. The main classes of medication used by the interviewees were: antihypertensives, hypoglycemics and anxiolytics/antidepressants. Final considerations: Through this research, the importance of using tools that help in pharmaceutical assistance and care in the hospital area was reinforced. However, there are still few studies on the subject. In view of this, it is suggested that future research be carried out, including at a national level, that seek to gather more evidence about the application of tools that guarantee safe and effective pharmaceutical care.